Providing Feedback in English Language Teaching - Petrová, Eliška (Univerzita Pardubice, 2018)
This diploma thesis deals with the issue of feedback provision in the lessons of English. The theoretical part introduces the system of aims, describes associated terminology and emphasizes the importance of interaction with objectives in the learning process. Next, the introduction of feedback follows, which is closely related to previously mentioned interaction. The term is defined and investigated from various points of view, while the alignment of feedback and aims is emphasized. Feedback classification is described and specific aspects of its content are stated. Also, strategies and techniques for feedback provision are suggested. This thesis emphasizes the importance of learners' active participation in feedback provision. The practical part presents an action research, which investigates feedback provision in lessons of English.
Poskytování zpětné vazby ve výuce anglického jazyka
Keywords: učitelé jako facilitátoři; cíle; interakce s dílčími cíli; zpětná vazba; elaborace; strategie; sebehodnocení; scaffolding; akční výzkum; facilitators; aims; interaction with objectives; feedback; alignment; learning strategies; formative feedback; self-assessment; scaffolding; action research